Lincoln in his own time : a biographical chronicle of his life, drawn from recollections, interviews, and memoirs by family, friends, and associates - Lincoln, Abraham, 1809-1865; Bush, Harold K. (Harold Karl), 1956-2021 (Writers in their own time (University of Iowa Press), 2011)
More than any other American before or since, Abraham Lincoln had a way with words that has shaped our national idea of ourselves. Actively disliked and even vilified by many Americans for the vast majority of his career, this most studied, most storied, and most documented leader still stirs up controversy. Showing not only the development of a powerful mind but the ways in which our sixteenth president was perceived by equally brilliant American minds of a decidedly literary and political bent, Harold K. Bush's Lincoln in His Own Time provides some of the most significant contemporary.